Socio-Demographic and Clinical Characteristics of Psychiatric Patients Who Have Committed Suicide: Analysis of Bulgarian Regional Suicidal Registry for 10 Years - Stoychev, Kaloyan; Dimitrova, Emilia; Nakov, Vladimir; Stoimenova-Popova, Maya; Chumpalova, Petranka; Veleva, Ivanka; Mineva-Dimitrova, Eleonora; Dekov, Dancho (Frontiers in Psychiatry, 2021)
Introduction Suicide is a major public health problem but factors determining suicide risk are still unclear. Studies in this field Bulgaria are limited, especially on a regional level. Methods By a cross-sectional design, we accessed the medical records of all psychiatric patients committed suicide over a 10-year period (2009-2018) in one major administrative region of Bulgaria. A statistical analysis was performed of the association between age of suicide as an indirect yet measurable expression of the underlying suicidal diathesis and a number of socio-demographic and clinical characteristics. Results 77 of 281 suicides (28%) had psychiatric records. Most common diagnoses were mood disorders (44%), followed by schizophrenia (27%), anxiety disorders (10%), substance use disorders (9%) and organic conditions (8%). Male gender, single/divorced marital status, early illness onset, co-occurring substance misuse and lower educational attainment (for patients aged below 70) were significantly associated with earlier age of suicide whereas past suicide attempts and psychiatric hospitalizations, comorbid somatic conditions and unemployment showed insignificant association. Substantial proportion of patients (60%) had contacted psychiatric service in the year preceding suicide, with nearly half of these encounters being within 30 days of the accident. Conclusion Severe mental disorders are major suicide risk factor with additional contribution of certain socio-demographic and illness-related characteristics. Monitoring for suicidality must be constant for chronic psychiatric patients. Registration of suicide cases in Bulgaria needs improvement in terms of information concerning mental health. More studies with larger samples and longitudinal design are needed, to further elucidate distal and proximal suicide risk factors.